Research on the Expression of Human Emotion in Fiber Art in the Post-epidemic Era: – A Case Study of the Work "Breaking Cocoon into Butterfly" - Ma, Xinran; Xiao, Zhixuan (Transactions on Social Science, Education and Humanities Research, 2023)
With the continuous development of technological innovation, fiber art has been more and more familiar to the public. Today, it has become a pluralistic and comprehensive subject. The infinite openness of fiber art provides a broad space for artists to explore diversified fiber materials and develop novel art forms. Grasping the characteristics of the overall beauty of modern fiber art, according to the rules of formal beauty, the mining and application of expression forms, materials, texture composition and texture design, creation materials, performance style, color shaping and space combination are the source of artists’ design and creation. In order to explore the changes of social and humanistic feelings during the epidemic, the idea of pursuing the beautiful vision after the reset of the heart is to integrate the personal emotion into the fiber. Around the theme of the reset and release, the composition of plant fiber was carried out on the graduation works of creative design, using the intuitive post-modern design style, will parse existing theme elements reconstruction, as well as the application of fiber, with fibre has spread to the properties of temperature into the emotional functions given in this work, and make public feel want to convey the profound connotation of works, Bring more interesting and rich visual experience for people.